2014
DOI: 10.1111/avj.12271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of anthelmintic resistance in ovine gastrointestinal nematodes in Australia (2009–2012)

Abstract: This compilation of results of FECRTs conducted by Australian parasitology laboratories in 2009-12 showed widespread AR of the common sheep nematodes (Teladorsagia, Trichostrongylus and Haemonchus) to all broad-spectrum anthelmintics, with the exception of monepantel, whether used singly or in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 18 publications
1
27
0
2
Order By: Relevance
“…AHR in small ruminants has been reported in various regions of world: Argentina (EDDI et al, 1996); Uruguai (NARI et al, 1996;BONINO & MEDEROS, 2003), Paraguai (MACIEL et al, 1996); South Africa ( VAN WYK et al, 1997); Mexico (TORRES-ACOSTA et al, 2003); Australia (SUTER et al, 2004;PLAYFORD et al, 2014) (ZANZANI et al, 2014);Ireland (KEANE et al, 2014); France, Greece and Italy (GEURDEN et al, 2014). The countries with the largest number of cross-sectional studies over time are New Zealand, the United Kingdom and Brazil (FALZON et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…AHR in small ruminants has been reported in various regions of world: Argentina (EDDI et al, 1996); Uruguai (NARI et al, 1996;BONINO & MEDEROS, 2003), Paraguai (MACIEL et al, 1996); South Africa ( VAN WYK et al, 1997); Mexico (TORRES-ACOSTA et al, 2003); Australia (SUTER et al, 2004;PLAYFORD et al, 2014) (ZANZANI et al, 2014);Ireland (KEANE et al, 2014); France, Greece and Italy (GEURDEN et al, 2014). The countries with the largest number of cross-sectional studies over time are New Zealand, the United Kingdom and Brazil (FALZON et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Globally; however, use of synthetic drugs for animal health and production is facing challenges due to a variety of factors, e.g., because of their high costs (Mondal et al, 2013), general toxicity (Patel et al, 2013), drug residual problems in milk and meat (Elmanama and Albayoumi, 2016;Tochi et al, 2016) and development of drug resistance in ticks (Abbas et al, 2014;Coles and Dryden, 2014;Heath and Levot, 2015;Kumar and Partap, 2015;Muyobela et al, 2015;Vudriko et al, 2016) and GIN (Playford et al, 2014;Alonso-Diaz et al, 2008;Borges et al, 2015;Geurden et al, 2015;Muniz-Lagunes et al, 2015;Ramos et al, 2016). In addition, quality of antiparasitic drugs, particularly in developing countries, has led to attention of the stakeholders to find alternatives, may be as a part of drug resistance management programs (Zaman et al, 2012a,b;Sindhu et al, 2014;Ghosh et al, 2015a;Kumar et al, 2016).…”
Section: Control Of Parasitismmentioning
confidence: 99%
“…Results of earlier studies suggested that a BCS-based TST approach is likely to have particular application in Mediterranean environments in Australia, where routine strategic treatments in the hot and dry summer period contribute strongly to the development (both prevalence and severity) of anthelmintic resistance (Besier and Love, 2003;Playford et al, 2014). Also, earlier computer simulation modelling suggests that for a single treatment given in summer in this environment, leaving even a small percentage of adult sheep untreated can provide a significant amount of refugia for non-selected worms, hence delaying anthelmintic resistance (Dobson et al, 2011).…”
Section: The Use Of Bcs As a Tst Selection Index Has Been The Subjectmentioning
confidence: 99%
“…and Teladorsagia circumcincta) have become increasingly difficult to effectively control. Resistance to the benzimidazoles and levamisole anthelmintics in several nematode genera is widespread, and macrocyclic lactone resistance in T. circumcincta is present on the majority of sheep properties (Playford, et al 2014).…”
Section: Introductionmentioning
confidence: 99%